PENDIDIKAN JASMANI BERBASIS HADIS DALAM PENDIDIKAN ISLAM: Relevansi dan Implementasi - Celine, Devi Rofidah; Kurjum, Mohammad (TARBIYA ISLAMIA : Jurnal Pendidikan dan Keislaman, 2024)
Physical education, which is often overlooked, has great potential to enrich Islamic religious education. The relationship between the two is often overlooked, even though Islam emphasizes the importance of balance between the physical and the spiritual. This study aims to reveal the relevance of physical education in the context of Islamic religious education by conducting a conceptual review of related hadiths. Through an in-depth analysis of a number of hadiths, this study attempts to find the theological basis that supports the integration of physical education in the religious learning process. The research method used is a literature study with a focus on authentic hadiths that discuss health, cleanliness, and physical activity. Data analysis was carried out using a thematic approach, namely by identifying the main themes that appear in the hadiths. The results of the study show that the hadiths of the Prophet Muhammad SAW explicitly emphasize the importance of maintaining physical health as a form of gratitude to Allah SWT. In addition, the hadiths also teach about ethics in exercising and the importance of maintaining cleanliness. Based on the results of the study, it can be concluded that physical education has a very high relevance in Islamic religious education. Physical activity is not only beneficial for physical health, but can also improve the quality of worship and strengthen faith. The integration of physical education in Islamic religious education can be one of the efforts to form a young generation that is physically and mentally healthy.